Greater muscle damage in athletes with ACTN3 R577X (RS1815739) gene polymorphism after an ultra-endurance race: a pilot study - T Belli; AH Crisp; R Verlengia (Biology of Sport, 2017)
In this study, we aimed to investigate the influence of ACTN3 R577X gene polymorphism on muscle damage responses in athletes competing in an ultra-endurance race. Twenty moderate to well-trained ultra-runners who had entered in an official 37.1 km adventure race (22.1 km mountain biking, 10.9 km trek¬king, 4.1 km water trekking, 30 m rope course, and orienteering) volunteered for the study. Blood samples were collected for genotyping and analysis of muscle protein levels before and after the race. Percentage changes (pre- to post-race) of serum myoglobin [XX = 5,377% vs. RX/RR = 1,666%; P = 0.005, effect size (ES) = 1.73], creatine kinase (XX = 836.5% vs. RX/RR = 455%; P = 0.04, ES = 1.29), lactate dehydrogenase (XX = 82% vs. RX/RR = 65%; P = 0.002, ES = 1.61), and aspartate aminotransferase (XX = 148% vs. RX/RR = 75%; P = 0.02, ES = 1.77) were significantly greater for XX than RX/RR genotypes. ES analysis confirmed a large magnitude of muscle damage in XX genotype ultra-runners. Therefore, athletes with the ACTN3 577XX genotype experienced more muscle damage after an adventure race. This suggests that ultra-runners with alpha-actinin-3 deficiency may be more susceptible to rhabdomyolysis and associated health complications during ultra-endurance com¬petitions.